Elemental composition and bioaccessibility of farmed oysters (Crassostrea gigas) fed different ratios of dietary seaweed and microalgae during broodstock conditioning. Issue 8 (28th June 2019) - Cardoso, Carlos; Gomes, Romina; Rato, Ana; Joaquim, Sandra; Machado, Jorge; Gonçalves, José Fernando; Vaz‐Pires, Paulo; Magnoni, Leonardo; Matias, Domitília; Coelho, Inês; Delgado, Inês; Castanheira, Isabel; et al.
Abstract: The Pacific oyster ( Crassostrea gigas ) culture has been expanding, thereby leading to a greater importance of hatcheries. Broodstock conditioning is very important in the hatchery process, in which diet composition may have a strong influence on the offspring production and quality. Therefore, the current study evaluated elemental composition and bioaccessibility of oysters fed different ratios of dietary seaweed (SW) and microalgae. The dietary conditioning consisted of direct replacement of microalgae by SW at four substitution levels (0%, 25%, 50%, and 100% diet). It was observed that oysters fed 100% SW had the highest levels of Be, Cu, Zn, Sr, and Cd. The most important trend was a concentration decline of most elements with progressively lower levels of SW substitution for microalgae in the feeds. No Cd or Pb hazard (contents below 1.0 mg/kg for Cd and 1.5 mg/kg for Pb) was found in oyster meat. Regarding elemental bioaccessibility, values were similar, near 100% in the cases of Cu, Br, and I. Only for Mn and Pb, bioaccessibility percentages deviated more from 100%. Indeed, the value for Pb was 50% ± 7% (initial group), and for Mn, all values were equal or lower than 29% ± 2% (final group of oysters fed microalgae). It was observed that Mn, Cd, and Pb bioaccessibility increased with a growing share of microalgal biomass in the feed. Therefore, this study showed that SW incorporation into the feed influences elemental composition and bioaccessibility of the oysters. Abstract : The most important trend was a concentration decline of most elements with progressively lower levels of SW substitution for microalgae in the feeds. No Cd or Pb hazard (contents below 1.0 mg/kg for Cd and 1.5 mg/kg for Pb) was found in oyster meat. This study showed that SW incorporation into the feed influences elemental composition and bioaccessibility of the oysters.